2000
DOI: 10.1007/s002230050006
|View full text |Cite
|
Sign up to set email alerts
|

Activity Increase After Extraction of Alkaline Phosphatase from Human Osteoblastic Membranes by Nonionic Detergents: Influence of Age and Sex

Abstract: The solubilization of alkaline phosphatase (AP) from osteoblastic cell membranes obtained from human primary bone cell cultures was studied according to the age and sex of the donors (17 females, 11 males; age range: 2-77 years). Cell membranes were treated by non-ionic (n-octyl beta-D-glucopyranoside, OG), ionic or zwitterionic detergents, then centrifuged. When OG was used almost all the AP was solubilized. AP activity in supernatant of solubilization was compared to the activity of the suspension before cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Various amounts of cellular components were detectable in the ECM. Particularly, ALP as a representative for membrane proteins17–19 was removed only incompletely. This will be true also for other proteins, like intercellular adhesion molecules and major histocompatibility antigens 37, 38.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various amounts of cellular components were detectable in the ECM. Particularly, ALP as a representative for membrane proteins17–19 was removed only incompletely. This will be true also for other proteins, like intercellular adhesion molecules and major histocompatibility antigens 37, 38.…”
Section: Discussionmentioning
confidence: 99%
“…ALP (EC 3.1.3.1) is the specific enzyme of bone forming cells. It is localized in the cell membrane of osteoblasts17–19 and matrix vesicles 20, 21. The detectable activity of this enzyme indicates remaining membrane components after the NH 4 OH treatment.…”
Section: Methodsmentioning
confidence: 98%
“…The proteins were separated using ultra-centrifugation filters with a molecular weight cut-off of 100 kDa (Amicon Ultra; MilliporeSigma). The enzymatic activity was evaluated in the >100 kDa protein fraction as human bone-specific ALP has an approximate weight of 140 kDa (30). The total protein was quantified according to the modified method of Lowry (31).…”
Section: Protein Expression In the Mineralised Matrixmentioning
confidence: 99%
“…the different solubilization of TNAP from osteoblast plasma membrane, obtained from human primary bone cell culture, it was suggested that changes in TNAP activity result from age-related modifications. These changes could be associated with the posttranslational modification of TNAP or with the membrane constituents (Radisson et al, 1996;Bourrat et al, 2000). The role of TNAP in mineral formation was evidenced in the case of hypophosphatasia, an inheritable disorder leading to a defective bone formation and characterized by a deficiency in TNAP (Whyte, 1994).…”
Section: Alkaline Phosphatase and Related Proteins In The Matrix Vesimentioning
confidence: 99%